Dengue: a continuing global threat. - Guzman, MG; Halstead, S; Artsob, H; Buchy, P; Farrar, J; Gubler, D; Hunsperger, E; Kroeger, A; Margolis, H; Martínez, E; Nathan, M; Pelegrino, J; et al. (2010)
Dengue fever and dengue haemorrhagic fever are important arthropod-borne viral diseases. Each year, there are ∼50 million dengue infections and ∼500,000 individuals are hospitalized with dengue haemorrhagic fever, mainly in Southeast Asia, the Pacific and the Americas. Illness is produced by any of the four dengue virus serotypes. A global strategy aimed at increasing the capacity for surveillance and outbreak response, changing behaviours and reducing the disease burden using integrated vector management in conjunction with early and accurate diagnosis has been advocated. Antiviral drugs and vaccines that are currently under development could also make an important contribution to dengue control in the future.